An Offering of Grain: The Agricultural and Spiritual Cycle of a Food System in the Kailash Sacred Landscape, Darchula, Far Western Nepal - Castagnetti, Francesca; Bhatta, Jagdish; Greene, Alexander (Frontiers in Sustainable Food Systems, 2021)
Foodscapes are commonly embedded in spiritual landscapes, making the spiritual dimension of local and indigenous food systems an important element of food sovereignty. However, this dimension is often overlooked in food systems research and policy making. Based on ethnobiological fieldwork conducted in the Kailash Sacred Landscape of far western Nepal, we show how religious festivals and rituals reenact the covenant between people and the land through the numinous intercession of Hindu gods and landscape deities. To demonstrate this, we present the local calendar of the agricultural and ritual year based on data collected through household surveys and participation in festivals and agricultural activities. The complex fabric of the local agri-food system is revealed as articulated in the warp and weft of interwoven agricultural and spiritual cycles. These cycles contribute to respectful and sustainable landscape management practices by shaping the relationship people have with the land. In the annual women's festival of Gaura, the fertility and well-being of people and land is affirmed through the offering of locally produced pulses and grains. Furthermore, local gastronomic identity is enriched by the incentive to cultivate heirloom varieties of crops that are prescribed in rituals performed during Gaura and other major festivals. We conclude that spiritual practices should be considered key elements of biocultural diversity, and recommend that they receive more attention in the implementation of sustainable development that aims to embody the principles of food sovereignty.